1996
DOI: 10.1007/bf01718165
|View full text |Cite
|
Sign up to set email alerts
|

Ebola virus infection in guinea pigs: presumable role of granulomatous inflammation in pathogenesis

Abstract: An approach combining virology with light and electron microscopy was used to study the organs of guinea pigs during nine serial passages of Ebola virus, strain Zaire. It was observed that the wild type of Ebola virus causes severe granulomatous inflammation in the liver and reproduces in the cells of the mononuclear phagocyte system (MPS). Based on morphological characterization, two types of virus-cell interactions were demonstrated. The obtained data evidenced for heterogeneity of the population of wild typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 15 publications
6
102
0
Order By: Relevance
“…This evidence suggests that hepatocyte apoptosis occurs during EBOV infection. Necrotic hepatocytes were also observed (data not shown), confirming earlier reports (6,(23)(24)(25).…”
Section: Indication Of Ebov-induced Hepatocyte Apoptosissupporting
confidence: 91%
See 1 more Smart Citation
“…This evidence suggests that hepatocyte apoptosis occurs during EBOV infection. Necrotic hepatocytes were also observed (data not shown), confirming earlier reports (6,(23)(24)(25).…”
Section: Indication Of Ebov-induced Hepatocyte Apoptosissupporting
confidence: 91%
“…Severe liver dysfunction is a hallmark of lethal EBOVinfection, as evidenced by hepatocyte death and accumulation of the liver enzymes ASTand ALTin theblood (15)(16)(17). Hepatocyte necrosis has been described in EBOV infection and may be a direct consequence of extensive viral replication in these cells (6,(23)(24)(25). However, apoptotic cell death of hepatocytes in EBOVinfected mice has not been reported.…”
Section: Indication Of Ebov-induced Hepatocyte Apoptosismentioning
confidence: 99%
“…Guinea pigs inoculated with wild-type EBOV develop only a short-lived, nonlethal febrile illness Bowen et al, 1980;Ryabchikova et al, 1996). A lethal guinea pig model for EBOV infection was developed eventually by infecting inbred and outbred guinea pig strains with ZEBOV, followed by sequential passages (4-8 times) of virus in naïve guinea pigs Bowen et al, 1980;Conolly et al, 1999;Ryabchikova et al, 1996) (Table 1).…”
Section: Guinea Pig Modelsmentioning
confidence: 99%
“…While rodents clearly have utility as models of filoviral disease, we recently showed that rodent models of EBOV HF are not ideal for studying human EBOV HF ; others have suggested that guinea pigs are inadequate for analyzing the pathogenesis of human EBOV HF (Ryabchikova et al, 1996). More specifically, neither mice nor guinea pigs exhibit the hemorrhagic manifestations that characterize primate EBOV infections.…”
Section: Introductionmentioning
confidence: 99%